2020
DOI: 10.2308/jmar-52479
|View full text |Cite
|
Sign up to set email alerts
|

Performance Incentives, Divergent Thinking Training, and Creative Problem Solving

Abstract: Creativity theory suggests that effective solutions to creative problems depend on both divergent and convergent thinking (Cropley 2006). Using an experiment in which participants solve insight problems, I investigate the effect of incentive schemes on creative problem-solving performance. I find that both piece-rate pay and a flat wage plus public recognition generate higher performance with divergent thinking training than without. Consistent with the idea that incentives may promote more convergent thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Divergent thinking promotes problem solving because it opens the mental spectrum, involves going beyond obvious, hackneyed, and conventional mental associations, and helps to find ideas of a more remote and unusual character. This link between DT and problem solving is widely contrasted (e.g., Huo, 2020;Runco, 2010;Saleh, 2019). Then, what is happening in our results?…”
Section: Discussionmentioning
confidence: 99%
“…Divergent thinking promotes problem solving because it opens the mental spectrum, involves going beyond obvious, hackneyed, and conventional mental associations, and helps to find ideas of a more remote and unusual character. This link between DT and problem solving is widely contrasted (e.g., Huo, 2020;Runco, 2010;Saleh, 2019). Then, what is happening in our results?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we inferred that if path searching in the problem space was needed in the process of problem solving (e.g., divergent problem solving), solving such problems could be related to spatial abilities. The typical divergent problems were the alternative uses task, and to solve such problems, the participants must think of as many alternative uses of a common object as possible, such as a brick (Duan et al, 2020; Huo, 2020; Jones et al, 2011). Previous studies have shown that spatial abilities are also closely associated with divergent problem solving (Liberman et al, 2012; Palmiero & Srinivasan, 2015).…”
Section: Discussionmentioning
confidence: 99%